CHROMATOGRAPHIC CHARACTERISATION OF POLYPYRROLE-BASED CONDUCTIVE POLYMER - Hawick Chriswanto (Scientific Contributions Oil and Gas, 1999)
A chromatographic study on the properties of polypyrrole-based conductive polymers has been carried out. The polymers were chemically axidantively prepared and coated directly onto silica particles and packed under high pressure into stainless steel chromatography columns. A series of small molecules were used as test compounds and chromatographic measurements were performed under reserved phase condition. The study revealed the properties of the polymers, such as their hydrophobicity, which were deduced from their behaviour in the interactions with the test compounds.